2020
DOI: 10.1002/ijgo.13456
|View full text |Cite
|
Sign up to set email alerts
|

FIGO Statement: Vaccination in pregnancy

Abstract: Pregnant women and their fetuses are among the vulnerable populations that can be severely affected by communicable diseases. As such, some vaccines such as the influenza and the Tdap (tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis) vaccines are strongly recommended in each pregnancy, with generally safe profiles. Other vaccines can be offered based on risk factors, and only when the benefits of receiving them outweigh the risks. Development of vaccines against group B streptococcus infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
1
11
0
1
Order By: Relevance
“…The vaccine has a good safety pro le and no studies have shown an association with any adverse pregnancy outcomes 34 . The reality is that the vaccination rate of pregnant women is still very low in various countries in the world 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine has a good safety pro le and no studies have shown an association with any adverse pregnancy outcomes 34 . The reality is that the vaccination rate of pregnant women is still very low in various countries in the world 35 .…”
Section: Discussionmentioning
confidence: 99%
“…FIGO's SMNH Committee endorses the recommendations to vaccinate all pregnant women against influenza during the influenza season irrespective of gestational age, and against Tdap (tetanus, diphtheria, pertussis)preferably between the 27th and 36th weeks of pregnancy in each pregnancy. 1 The crucial role of healthcare workers, particularly obstetricians, in promoting maternal vaccination is stressed-especially since women are up to 50 times more likely to accept vaccination if the recommendation is made by their obstetrician. 2 It was hoped that the introduction of Anti-Rh(D) immunoglobulin in 1968 would lead to the eradication of rhesus disease.…”
Section: A Framework For Safe Obstetrical Practicesmentioning
confidence: 99%
“…Adult immunization has not been meeting the global elimination targets due to several factors, and this is particularly evident in pregnant women who are considered a vulnerable population that can be severely affected by communicable diseases. FIGO’s SMNH Committee endorses the recommendations to vaccinate all pregnant women against influenza during the influenza season irrespective of gestational age, and against Tdap (tetanus, diphtheria, pertussis)—preferably between the 27th and 36th weeks of pregnancy in each pregnancy 1 . The crucial role of healthcare workers, particularly obstetricians, in promoting maternal vaccination is stressed—especially since women are up to 50 times more likely to accept vaccination if the recommendation is made by their obstetrician 2 …”
mentioning
confidence: 99%
“…De manera general, se puede afirmar que la inmunización de la gestante implica la protección del feto por dos situaciones específicas: primero, la prevención del desarrollo de una enfermedad severa en la madre y, segundo, la protección del feto gracias al paso transplacentario de IgG 16 . Las recomendaciones de inmunización durante la gestación resaltan la necesidad de usar vacunas muertas, inactivadas o de partes dado que no tendrían potencial de reactivación ni de infección, a diferencia de las vacunas vivas 17 .…”
Section: Vacunación Durante El Embarazounclassified